Peptide asparaginyl ligases—renegade peptide bond makers - Tam, James P. (2021)
Making peptide bonds is tightly controlled by genetic code and machinery which includes cofactors, ATP, and RNAs. In this regard, the stand-alone and genetic-code-independent peptide ligases constitute a new family of renegade peptide-bond makers. A prime example is butelase-1, an Asn/Asp(Asx)-specific ligase that structurally belongs to the asparaginyl endopeptidase family. Butelase-1 specifically recognizes a C-terminal Asx-containing tripeptide motif, Asn/Asp-Xaa-Yaa (Xaa and Yaa are any amino acids), to form a site-specific Asn-Xaa peptide bond either intramolecularly as cyclic proteins or intermolecularly as modified proteins. Our work in the past five years has validated that butelase-1 is a potent and versatile ligase. Here we review the advances in ligases, with a focus on butelase-1, and their applications in engineering bioactive peptides and precision protein modifications, antibody-drug conjugates, and live-cell labeling.